The VALID‐CRT risk score reliably predicts response and outcome of cardiac resynchronization therapy in a real‐world population. Issue 10 (13th July 2019) - Bertaglia, Emanuele; Arena, Giuseppe; Pecora, Domenico; Reggiani, Albino; D'Onofrio, Antonio; Palmisano, Pietro; De Simone, Antonio; Caico, Salvatore I.; Marini, Massimiliano; Maglia, Giampiero; Ferraro, Anna; Solimene, Francesco; et al.
Abstract: Objectives: The aim of the study was to confirm the value of the VALID‐cardiac resynchronization therapy (CRT) risk score in predicting outcome and to assess its association with clinical response (CR) in an unselected real‐world CRT population. Methods and Results: The present analysis comprised all consecutive CRT patients (pts) enrolled in the CRT‐MORE registry from 2011 to 2013. Pts were stratified into five groups (quintiles 1‐5) according to the VALID‐CRT risk predictor index applied to the CRT‐MORE population. In the analysis of clinical outcome, adverse events comprised death from any cause and non‐fatal heart failure (HF) events requiring hospitalization. CR at 12‐month follow‐up was also assessed. We enrolled 905 pts. During a median follow‐up of 1005 [627‐1361] days, 134 patients died, and 79 had at least one HF hospitalization. At 12 months, 69% of pts displayed an improvement in their CR. The mean VALID‐CRT risk score derived from the CRT‐MOdular Registry (MORE) population was 0.317, ranging from −0.419 in Q1 to 2.59 in Q5. The risk‐stratification algorithm was able to predict total mortality after CRT (survival ranging from 93%‐Q1 to 77%‐Q5; hazards ratio [HR] = 1.42, 95% confidence interval [CI]: 1.25‐1.61, P < .0001), and HF hospitalization (ranging from 95% to 90%; HR = 1.24, 95% CI: 1.06‐1.45, P = .009). CR was significantly lower in pts with a high‐to‐very high risk profile (Q4‐5) than in pts with a low‐to‐intermediate risk profile (Q1‐2‐3) (55% vs 79%, P < .0001). Conclusion: The VALID‐CRT risk‐stratification algorithm reliably predicts outcome and CRT response after CRT in an unselected, real‐world population.